Applying a Mathematical Model to Compare, Choose, and Optimize the Management and Economics of Milking Parlors in Dairy Farms - Alessandro Chiumenti; Francesco da Borso; Roberto Chiumenti; Pavel Kic (Agriculture, 2020)
Dairy farms are growing in several areas of the world, with consequent need for a modernization of milking equipment. The objective of this research is to evaluate milking parlors in current and future situations in modern farms. Several Italian farms were studied: three farms with side-by-side milking parlors (50 cows, 82 cows, and 100 cows), two with herringbone milking parlors (70 cows and 90 cows) and two with rotary milking parlors (360 cows and 900 cows). The choosing and evaluation of milking parlor parameters is based on results of previous research, using the mathematical model developed in the Czech University. The time for milking and the final specific direct costs are the main parameters which enable evaluation and choosing of suitable milking parlor from the dairy; neglect or promotion of only one of the mentioned criteria may lead to uneconomic investment or impaired operation of a farm. The evaluation of existing milking parlors can help to enhance the milking process and operations from the point of view of either technical improvement or improved activity of milkers. The results of measurement and calculation in current farms are compared with possible future enlarged farms. The study demonstrated that increasing the capacity of dairy farms enables a reduction of the final specific direct costs for milking.